Anti-SARS-CoV-2 IgA Identifies Asymptomatic Infection in First Responders. (12th October 2021) - Montague, Brian T; Wipperman, Matthew F; Hooper, Andrea T; Hamon, Sara C; Crow, Rowena; Elemo, Femi; Hersh, Lisa; Langdon, Shaun; Hamilton, Jennifer D; O'Brien, Meagan P; Simões, Eric A F
Abstract: Background: Immunoglobulin A (IgA) is an important component of the early immune response to SARS-CoV-2. Prior serosurveys in high-risk groups employing IgG testing alone have provided discordant estimates. The potential added benefit of IgA in serosurveys has not been established. Methods: Longitudinal serosurvey of first responders (police, emergency medical service providers, fire fighters, and other staff) employing 3 serologic tests (anti-spike IgA, anti-spike IgG, and anti-nucleocapsid IgG) correlated with surveys assessing occupational and nonoccupational risk, exposure to COVID-19, and illnesses consistent with COVID-19. Results: Twelve percent of first responders in Colorado at baseline and 22% at follow-up were assessed as having SARS-CoV-2 infection. Five percent at baseline and 6% at follow-up were seropositive only for IgA. Among those IgA positive only at baseline, the majority (69%) had a positive antibody at follow-up; 45% of those infected at baseline and 33% at follow-up were asymptomatic. At all time points, the estimated cumulative incidence in our study was higher than that in the general population. Conclusions: First responders are at high risk of infection with SARS-CoV-2. IgA testing identified a significant portion of cases missed by IgG testing and its use as part of serologic surveys may improve retrospective identification of asymptomatic infection. Abstract : In a serosurvey of high-risk first responders, detection of IgA in the absence of detectable IgG identified individuals with mild or asymptomatic infection, which would have been missed based assessment of anti-spike or anti-nucleocapsid IgG.